Accuracy of lung and diaphragm ultrasound in predicting infant weaning outcomes: a systematic review and meta-analysis - Gao, Yang; Yin, Hong; Wang, Mei-Huan; Gao, Yue-Hua (Frontiers in Pediatrics, 2023)
About 30% of patients in pediatric intensive care units require mechanical ventilation, and doctors have struggled with the timing of weaning. In recent years, lung and diaphragm ultrasound have been acknowledged as an excellent method for predicting weaning results in adults. We summarized 11 research on the use of lung and diaphragm ultrasound in weaning children in this study, and we concluded that lung and diaphragm ultrasound is also a good technique for predicting weaning results in children. The sensitivity and specificity of lung ultrasound scores were 0.88 (95% CI, 0.85-0.90) and 0.81 (95% CI, 0.75-0.87), respectively. Diaphragm thickening fraction (DTF) outperformed diaphragmatic excursion (DE) as a predictor of diaphragm ultrasonography, with the diagnostic odds ratio (DOR) of DTF being 28.35 (95% CI,). This study backs up doctors' decision to use lung and diaphragm ultrasonography to predict weaning outcomes. At the same time, we believe that using bedside ultrasound can improve weaning success rates in MV children to some extent.